Variation of durability and physical performance of barium-calcium phosphoaluminate cement exposed to high temperature. (1st June 2022) - Yuan, Jungang; Huang, Yongbo; Yan, Jinghua; Wu, Fengnian; Du, Peng; Lu, Xiaolei; Liu, Hao; Wang, Shoude; Zhao, Piqi; Hou, Pengkun; Lu, Lingchao
Abstract: The influences of high temperature on the performance of cement cannot be ignored, but there was little research on the high-temperature resistance of barium-calcium phosphoaluminate cement (PABC) based on the phosphoaluminate cement (PAC) with the excellent mechanical properties. In this paper, the durability and physical performance of PABC after exposure to elevated temperatures were discussed through the analysis of XRD, SEM-EDS and pore structure. The experimental results indicated that the resistance to chloride ions penetration and sulfate attack decreased to varying degrees at elevated temperatures ranging from 100 °C to 300 °C. Besides, high temperatures ranging from 800 °C to 1200 °C worsened the performance of cement including compressive strength, mass loss ratio and water absorption ratio, but a rise in performance can be observed at 1400 °C due to the generation of a new phase and changes of pore structure. The changing rules presented on these performance were consistent as the temperatures elevated, which demonstrated the unique characteristics of PABC confronted with high temperatures. Highlights: The PABC could have the good sulfate resistance when the temperature was lower than 200 °C. The physical performance of cement decreased with the increase of exposure temperature, but a rise occurred due to the reduction of cement porosity at 1400 °C. The 7-day curing can almost get cement stone own the same water absorption ratio as 28-day curing.